Four new species of Collybiopsis (Omphalotaceae, Agaricales) from subtropical regions of China - Ling Ding; Ben-Jian Zhong; Hui Zeng; Sheng-Nan Wang; Jun-Qing Yan (MycoKeys)
Four new species of Collybiopsis, namely C. subpolygramma, C. fucata, C. dentata, and C. latispora, were discovered in the subtropical regions of China. These species were identified based on morphological characteristics and molecular analysis. Morphologically, C. subpolygramma is characterized by its pileal surface, white in color with a light brown center; slender, cylindrical cheilocystidia; and absence of pleurocystidia. C. fucata is recognized by the reddish-brown, hygrophanous pileus; adnate to adnexed lamellae; and relatively broad basidiospores. C. dentata is identified by free lamellae, fusiform to utriform pleurocystidia, and relatively broad basidiospores. C. latispora is distinct by relatively broad basidiospores and a minute, snow-white ring or ruff at the stipe base. In the phylogenetic analysis based on combined ITS and LSU sequences, the four new species formed distinct and stable branches (BI-PP = 1; ML-BP = 100%), respectively. Collybiopsis subpolygramma formed a sister lineage with C. polygramma. The new species C. fucata, C. dentata, and C. latispora were found to be nested within the C. ramealis species complex clade. Detailed descriptions, color photos, and a key to related species are presented.